A survey of the density, distribution, and Schistosoma japonicum infection of Oncomelania quadrasi collected in Brgy. Gacao, Brgy. Libertad, and Brgy. San Antonio, Palo, Leyte - Yaona, Yelena Donalli C.; Varona, Gracia F. (2016)
Three barangays in Palo, Leyte were surveyed for the presence of Oncomelaia quadrasi, the intermediate host of Schistosoma japonicum. The survey was conducted in Brgy. Gacao, Brgy. Libertad, and Brgy. San Antonio in November 2015 and February 2016. A total of nine collecting stations, three for each barangay, established. The presence of snail colonies were surveyed along streams, tributaries, canals and swampy areas. Intensive snail search and ring sampling method were employed for purposive and random sampling, respectively. The latter involved a 25 m2 quadrat while the former involved ring sampling thrown outside the 25 m2 area. Brgy. Gacao showed the highest average infection rate and average snail densite, while Brgy. San Antonio scored the lowest in both parameters. The number of snails found in a 25 m2 area ranged from 11 (Brgy. San Antonio Site 1) to 109 (Brgy. Gacao Site 1) while the number of infected nails ranges from 2 to 88. The number of snails found in a single ring sample was in the range 0-15. The number of infected snails in a single ring sample ranged from 0 to 9 while the most nmber of infection was observed in snails from Brgy. Libertad Site 3. Infection rate is affected by human schisstosomiasis infectioin rate and the sanitary measures employed by a particular area (establishment of zero-defecation zones) though studes show that there is no correlation between snail infection rate and human schistosomiasis infection rate. Snail density on the other hand is affected by environmental factors.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and technology